Phase 3 efficacy analysis of a typhoid conjugate vaccine trial in Nepal - Shakya, M; Colin-Jones, R; Theiss-Nyland, K; Voysey, M; Pant, D; Smith, N; Liu, X; Tonks, S; Mazur, O; Farooq, YG; Clarke, J; Hill, J; et al. (Massachusetts Medical Society, 2019)
BACKGROUND Salmonella Typhi is a major cause of fever in children in low- and middle-income countries. A typhoid conjugate vaccine (TCV) that was recently prequalified by the World Health Organization was shown to be efficacious in a human challenge model, but data from efficacy trials in areas where typhoid is endemic are lacking.